2007
DOI: 10.1021/ja074627u
|View full text |Cite
|
Sign up to set email alerts
|

Two- and Three-Dimensional Smectic Ordering of Single-Handed Helical Polymers

Abstract: Rodlike polymers with precisely defined architectures are ideal building blocks for self-assembled structures leading to novel nanometer-scale devices. We found that the living polymerization of a single isocyanide enantiomer bearing an l-alanine pendant with a long n-decyl chain simultaneously produced diastereomeric right- and left-handed helices with different molecular weights and narrow molecular weight distributions. Each single-handed, rodlike helical polymer with a controlled length and handedness isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(125 citation statements)
references
References 30 publications
(31 reference statements)
5
119
1
Order By: Relevance
“…In addition, the helical sense excesses of each polymer can be directly evaluated to be 97 and 99%, respectively, by counting the number of helical senses using high-resolution AFM (Figure 10b). 89 The isolated right-(P) and left-handed (M) helical L-20c and L-20d maintain their living polymerization activity, and the corresponding L-and D-isocyanide monomers were found to be further block copolymerized in a highly enantiomer-selective manner, whereby narrow molecular weight distributions were maintained. M-L-20d preferentially copolymerized the L-monomer over its D-enantiomer by a factor of 6.4-7.7.…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the helical sense excesses of each polymer can be directly evaluated to be 97 and 99%, respectively, by counting the number of helical senses using high-resolution AFM (Figure 10b). 89 The isolated right-(P) and left-handed (M) helical L-20c and L-20d maintain their living polymerization activity, and the corresponding L-and D-isocyanide monomers were found to be further block copolymerized in a highly enantiomer-selective manner, whereby narrow molecular weight distributions were maintained. M-L-20d preferentially copolymerized the L-monomer over its D-enantiomer by a factor of 6.4-7.7.…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
“…89 On the basis of high-resolution AFM, combined with XRD analysis, it is concluded that both right-and left-handed helical L-20c and L-20d possess a rigid rod 15/4 helix with a helical pitch of B1.3 nm assisted by four sets of intramolecular hydrogen bondings. In addition, the helical sense excesses of each polymer can be directly evaluated to be 97 and 99%, respectively, by counting the number of helical senses using high-resolution AFM (Figure 10b).…”
Section: Synthesis and Structures Of Helical Polymers E Yashimamentioning
confidence: 99%
“…Figure 5 shows the typical AFM phase images of poly(1L m -co-1D n ) deposited on highly oriented pyrolytic graphite (HOPG) from a dilute benzene solution (0.005 mg ml À1 ), followed by benzene vapor exposure at B25 1C for 12 h. 21,22 This method is also very useful for constructing highly ordered 2D helix bundles with a controlled helicity for a dynamically racemic helical poly(phenylacetylene) 23 and helical polyisocyanides [46][47][48] on HOPG, and their helical structures were visualized by AFM. 49 Poly(1L m -co-1D n ) self-assembled into regular 2D helix bundles with a constant height (B1.6 nm), and the copolymer chains packed parallel to each other.…”
Section: Amplification Of Macromolecular Helicity In Poly(phenylacetymentioning
confidence: 99%
“…In their subsequent work, the authors separated single-handed helices from racemic helices through facile treatment with acetone. 29 In 2006, Sakurai et al 30 reported a solvent-mediated helix transition. The helical structure of poly(phenylacetylene) underwent a pH-mediated transformation The pH value in aqueous media can easily be adjusted, which provides a convenient method for mediating the chirality of materials.…”
Section: Solvent-mediated Transformationmentioning
confidence: 99%
“…Furthermore, an enantiomer-selective and helix-sense-selective living block copolymerization of isocyanide enantiomers was realized by Wu et al 56 In the first stage, right (P)-and left (M)-handed helical poly(isocyanides) were prepared by a living polymerization of enantiomerically pure monomer L-1. 57 In the second stage, living block copolymerization of L-1 or D-1 was initiated by the as-prepared rigid M-poly-L-1 or P-poly-L-1 and proceeded in a highly enantiomerselective manner. The M-poly-L-1 preferentially copolymerized with L-1 over D-1 by a factor of 6.4-7.7; in contrast, the P-poly-L-1 preferentially copolymerized with D-1 over L-1 by a factor of 4.0.…”
Section: Chiral Interaction-induced Morphological Changes In Smart Pomentioning
confidence: 99%